Dampening Effects of Perceived Teacher Enthusiasm on Class-Related Boredom in College Students: Longitudinal Mediation Effects of Perceived Task Value - Guan-yu Cui (Frontiers in Psychology, 2021)
This study aims to explore the longitudinal mediation effects of college students’ perceived task value (PTV) between perceived teacher enthusiasm (PTE) and class-related boredom (CB). We conducted a longitudinal survey among college students from five colleges at the second (T1), sixth (T2), tenth (T3), and fourteenth week (T4) in a semester, and overall 1,371 students completed all the measurements. In the survey, a battery of questionnaires was used to measure the students’ PTE, perception of task difficulty, perception of task value, and CB. At T1, boredom proneness was measured as a control variable. Analysis of the longitudinal data showed that after controlling for the effects of boredom proneness and perceived task difficulty, students’ PTE was a significant predictor of CB, and students’ PTV played a significant mediating role in this causation relationship. The study supported the importance of the control-value theory in explaining the mitigating effect of students’ PTE on CB, especially highlighting the role of PTV.